The Effect of Work Relationships Career Development and Work Motivation on Job Satisfaction of Employees of the Yogyakarta City Land and Spatial Planning Office - Alghifari, Gallant (Jurnal Ekonomi Balance, 2023)
The purpose of this study itself is to determine the effect of career development on job satisfaction. Knowing the effect of work motivation on job satisfaction Knowing the effect of work relationships on job satisfaction. Knowing the effect of career development, work relationships and motivation on job satisfaction. researchers took samples by applying the non-probability method with saturated samples. The questionnaires that were processed amounted to 65 employees of the Yogyakarta City Land and Spatial Planning Office. The research shows that there is a relationship between the variables of work relationship, career development and work motivation on job satisfaction simultaneously or partially